The Separation Distance of the Diffraction Peak Angle between Main Planes (hkl) As an Indicator of the Orthorhombicity of the GdBa2Cu3O7-? Phase Crystal Lattice Structure - Permana, I Komang Wahyu Surya; Sumadiyasa, Made; Windarjoto, Windarjoto (BULETIN FISIKA; Vol 22 No 1 (2021): BULETIN FISIKA February EditionDO - 10.24843/BF.2021.v22.i01.p06, 2020)
The orthorombicity of a crystal lattice structure is indicated by the difference in lattice parameter values ??a, b and c. This study aims to show that the split distance value between the angles of the diffraction peaks of the two planes (hkl) closest is the same as the orthorombicity value crystal structure on the GdBa 2 Cu 3 O 7-?   phase. For this purpose, in this study, a compound Gd 0,85 La 0,15 Ba 2-x Sr x Cu 3 O 7-  has been synthesized with variations of x = 0.00, 0.05, 0.10, 0.20, 0.30 and 0.50. Samples were synthesized using a solid reaction method with wet mixing, sintered at a temperature of 900°C for 12 hours. From the results of XRD spectrum analysis with Match-3 and Rietica software, it is found that by the increasing the content of Sr the pattern of changes in the value of the split distance the angles of the diffraction peaks of (hkl) planes closest, the measurement and calculation results are the same with the changing pattern of the orthorombicity  value. The measurement and calculation results, the split distance value between the diffraction peaks angle for the plane of (020) and (200) is almost equal to one-tenth of the orthorombicity value. Thus, the split distance value between the angles of the diffraction peaks of the two (hkl) planes closest can be used as an indicator of the orthorombicity a GdBa 2 Cu 3 O 7-?   phase crystal structure.